Efektivitas Penggunaan Thread Lift Dengan Metode Jin’s 3 Needle Pada Overweight - Listina Ade Widya Ningtyas; Sri Widyastari; Kurnia Eka Putri (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Thread Lift Method, 3 Jinn Needles, Obesity. Excess body weight, normal weight, with waist circumference of 80-87 cm and BMI ≥ 23.0. Jin's 3-Needle is a method of acupuncture therapy using three dots. Thread Lifts on acupuncture points can increase the body's metabolism. The purpose of this study to determine the effectiveness of Thread Therapy Using Methods Jin's 3 Needle in patients Overweight. Pretest Experimental Design Postest Control Group. The research location is at SMP N 2 Colomadu in March-June 2017. The population is teachers and employees in SMPN 2 Colomadu which is 60 people. Dependent variable decreased waist circumference and BMI, variable. Thread with Jin's 3 Needle method. Samples of 33 people with purposive sampling technique. Data analysis in this study using unpaired T Test. The result showed that the average BMI before therapy was 27,15 kg/ m² and after therapy 26,71 kg/ m² (CI: 0,29 -0,60), with standard deviation 0,434. Average waist circumference results before therapy was 96.79 cm and after therapy 93.62 cm (CI: 2.40-3.93), with a standard deviation of 2.160. After the test, p value 0.001 <0.05 where Ho is rejected and Ha accepted. How to lift it with Jin's 3 Needle is effectively used on overweight.